A preliminary study on digital image performance to stimulate food taste experience - Nur Hasni Nasrudin; Afdallyna Fathiyah Harun (Institute of Advanced Engineering and Science, 2020)
Users and food marketers alike would share images of food in the hopes that viewers would be able to capture the emotion/sensation presented by the food. This is a form of food digitization, shifting away from the mechanical aspect of taste stimulation to the use of digitized visuals. This paper aim to evaluate the performance of taste perception made by users by just looking at food image. Using food images as a medium of taste stimulation, this paper reports international users’ perception of the taste of Malaysian local food through an online channel. By applying SPSS analysis, the author studied the patterns of similarity and dissimilarity of users’ perception of food images that have been compiled using an online survey. Interestingly observed, the results of the analysis enable the author to assess how close user perceptions were akin to the real taste. The author found that most user perceptions are closely matched with the food’s real taste which allows the author to conclude that visual media is possible in stimulating food taste experience. It is good news for food marketers and food tourism. Nevertheless, more samples of food images are required to further attest these findings.